Comparative Study of Polymerase Chain Reaction And Routine Microbiological Methods for the Diagnosis Of Pneumococcal Meningitis in Csf (Journal of Chittagong Medical College Teachers' Association, 2019)
Background: Bacterial meningitis is an important cause of mortality and long term morbidity. Early and accurate diagnosis of bacterial meningitis is of critical concern. Though bacterial culture is considered as gold standard, this approach has some disadvantages with regard to rapidity and sensitivity. This has motivated the evaluation of alternative diagnostic strategy. This study was performed to compare between Polymerase Chain Reaction (PCR) and conventional methods for the diagnosis of pneumococcal meningitis. Materials and Methods: This cross sectional study was carried out in the Department of Microbiology, Chattogram Medical College for cytological examination, biochemical tests, Gram’s stain, culture, and PCR for lytAgene of S.pneumoniae in CSF. Results: Among the 36 cases of probable bacterial meningitis, culture was positive in 12 (33.33%) and Gram’s stain was positive in 9 (25%) cases. Streptococcus pneumoniaewas the predominent organism detected by isolation in 6(50%). PCR detected 14(46.67%) cases of S. pneumoniae among 30 bacterial meningitis cases. All the culture and Gram’s stain positive cases for Streptococcus pneumoniaewere also positive by PCR. The sensitivity, specificity, positive predictive value and negative predictive value of PCR were 100%, 67%, 43%,100% respectively by using CSF culture as gold standard. Conclusion: PCR was highly sensitive and specific and PCR was found superior to other available methods for detection of bacterial meningitis.JCMCTA 2018 ; 29 (2) : 16-21